The impact of flower morphology and pollinator community composition on pollen transfer in the distylous Primula veris. (1st March 2018) - Deschepper, P; Brys, R; Jacquemyn, H
Abstract: Distyly is a ﬂoral polymorphism characterized by the presence of two discrete morphs with reciprocal positioning of anthers and stigmas in ﬂowers on different plants in the same population. For a distylous system to function effectively, the presence of suitable pollinators that transfer pollen from the two morphs (a short-styled S-morph and a long-styled L-morph) on separate locations of their body is required. In this study, we surveyed pollinator communities visiting flowers of the distylous Primula veris in two different natural habitats (grassland and forest). Previous research has shown differences in the positioning of the anthers and stigmas between flowers of forest and grassland populations, possibly impacting on patterns of pollen transfer and seed set. To test this hypothesis, we measured anther–stigma separation in the two habitats, assessed pollen uptake on the head and proboscis of each of the pollinator species observed, and compared stigmatic pollen deposition and subsequent seed set between short-styled and long-styled flowers of P. veris . More specifically, we tested the hypothesis that the ratio of pollen morph uptake by pollinators is related to the length of their proboscis and to differences in floral morphology and that this in turn is related to the efficiency with which legitimate pollen is deposited on S- and L-morph stigmas. The forest and grassland P. veris populations contained distinct pollinator communities. Pollen from L-morph flowers was more abundantly deposited on the proboscis than on the head of the pollinator, whereas the opposite was observed for pollen of short-styled flowers. Tongue length seemed to be a determining characteristic for the predisposition of a pollinator for pollen uptake of a certain pollen morph on the proboscis or head. Proboscis length was positively correlated with proportional uptake of pollen of long-styled flowers, but negatively correlated with the uptake of pollen of short-styled flowers on the head. Long-styled stigmas captured more pollen grains in total, but short-styled stigmas contained proportionally more legitimate pollen. Pollen proficiencies were higher in the grassland habitat, but seed set did not significantly differ between habitats. Overall, these results suggest that that long- and short-tongued insects complement each other in the legitimate pollination of a distylous plant species and that differences in floral morphology do not impact on reproductive success.